Business environment of dairy cattle farmers on cooperative positioning and its implications toward marketing performance - Dandan Irawan; Heri Nugraha; M Ardi Nupi Hasyim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The government has enacted the Republic of Indonesia Regulation Number 20 Year 2008 which discusses Micro, Small and Medium Enterprises (MSMEs). This legislation directs to overcome external problems faced by MSMEs and facilitates the opening of business opportunities in a manner. The researcher is interested in researching the Dairy Cattle Farmer's Business Environment on Cooperative Positioning and Its Implications toward Marketing Performance. This study aims to provide an overview of the development of dairy cattle business in West Java Province. This study uses a survey method which is a research method utilized to extract facts from existing symptoms and seek factual information (Nazir, 2005). In the survey method, data is collected from a sample of the population and using a questionnaire as the main data collection tool. The result of this study can be concluded that the external business environment, cooperative positioning affect the marketing performance of dairy farmers in West Java Province.